Critical Roles of VEGFR1, VEGFR2, VEGFR3, BAX, and BCL-2 in the Pathogenesis of Varicose Veins: Unveiling Molecular Mechanisms - Mehdi Abedinzadeh; Alireza Nazari; Seraj-Aldin Vahidi; Soheila Pourmasumi; Hossein Khorramdelazad (American Journal of Men's Health)
Varicocele is characterized by the abnormal dilation of veins within the testicular pampiniform plexus, contributing to inflammation, pain, and infertility in males. The precise roles of vascular endothelial growth factor receptors (VEGFRs), B-cell lymphoma 2 (BCL-2), and BCL-2-associated X-protein (BAX) in the pathology of varicocele still need to be clarified. This study sought to investigate the protein expression levels of VEGFR1, VEGFR2, VEGFR3, BCL-2, and BAX in varicose and healthy vessels from patients diagnosed with varicocele. Tissue samples were collected from 20 varicose veins and 20 healthy vessels from patients diagnosed with varicocele. Western blotting was utilized to quantify VEGFR1, VEGFR2, VEGFR3, BCL-2, and BAX protein levels. Analysis revealed a statistically significant increase in VEGFR3 protein expression within varicose veins compared to healthy vessels ( p = .0473), while no significant differences were observed in the levels of VEGFR1 and VEGFR2 between the two groups. Concerning apoptotic signaling proteins, no significant differences were noted in the individual expression levels of BAX and BCL-2; however, the BAX/BCL-2 ratio was approximately 1.29 in varicose vessels. This ratio, exceeding 1.0, may suggest a pro-apoptotic shift in varicose veins and indicates a potential involvement of apoptosis in the pathology of varicocele. These findings suggest that VEGFR3 may play a pivotal role in the pathogenesis of varicocele and could contribute to vascular alterations associated with this condition. Furthermore, the elevated BAX/BCL-2 ratio implies a pro-apoptotic environment within varicose veins, thereby implicating apoptosis as a possible mechanism in the development of varicocele. Further exploration of VEGFR3-related signaling pathways and apoptotic markers may yield valuable insights for identifying therapeutic targets in managing varicocele.